The Application of 5E Learning Cycle Model Towards Students Learning Activities on Salt Hydrolysis Subject Material in Grade XI SMAN 1 Pakem Academic Year 2019/2020 - Nisrina Zahira Putri Irawan; Muhaimin Muhaimin; Krisna Merdekawati (Universitas Islam Indonesia, 2021)
This study aims to determine whether there is a significant difference between the application of the 5E Learning Cycle model and conventional learning towards learning activities on salt hydrolysis subject material. The type of research used experimental research. The study population was all students of grade XI at SMA Negeri 1 Pakem in the academic year 2019/2020, totaling 5 classes. The research sample used XI MIPA 1 class as the experimental class and XI MIPA 2 class as the control class which was taken by purposive sampling technique. Data collection through non-test techniques in the form of questionnaires and observations. Data analysis techniques on learning activity variables used Parametric Statistics Independent Sample T-Test for observational data and Non-Parametric Statistics for the Mann-Whitney test for questionnaire data. Based on the results of the study, it can be concluded that there is a significant difference between students who take learning with the 5E Learning Cycle model and students who take conventional learning towards learning activities.